METHODOLOGICAL FEATURES OF COMPILING AND CONDUCTING CONTROL TASKS IN MATHEMATICS - Abdullayeva, Zh. B. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
The article is devoted to the study of methodological features of compiling and conducting control tasks in mathematics. Possible options for tests used to test students' knowledge, as well as the main tools in the preparation of control tasks, are considered. An algorithm for compiling and conducting control tasks in mathematics is provided.
Keywords: mathematics; control work; control tasks; methods of conducting control work